Gold‐Catalyzed Regioselective Oxyfluorination/Oxydifluorination vs. Diketonization of Phthalimido‐Protected Propargylamines with Selectfluor. Issue 29 (21st February 2022) - Marsicano, Vincenzo; Arcadi, Antonio; Michelet, Véronique
Abstract: Alkyl‐ and aryl‐substituted N ‐propargyl phthalimides were used as valuable building blocks for the selective formation of the corresponding α‐fluoro, β‐phthalimido ketones, α, α‐difluoro, β‐phthalimido ketones or β‐phthalimido α‐diketones by means of gold‐catalyzed oxyfluorination/oxydifluorination or dioxygenation reactions. The key factors addressing the product selectivity control were determined. The simultaneous assembly of the quinoxaline nucleus and the removal of the phthalimido‐protecting group were tested. Reaction mechanisms of the different reaction pathways are assumed. Abstract : The selective formation of α‐fluoro, β‐phthalimido ketones, α, α‐difluoro, β‐phthalimido ketones or β‐phthalimido α‐diketones is described by means of gold‐catalyzed oxyfluorination/oxydifluorination or dioxygenation reactions. The simultaneous assembly of the quinoxaline nucleus and the removal of the phthalimido‐protecting group were also performed.